From Lament to Drama – Analysis of “The laments on Ariyathi Wife of Vellappanikan” - Navadharshani, K. (Centre for Asian Studies, 2016)
It is the believed that “The lament on Ariyaathai wife of Vellappnikan” was composed during the Dutch period in the Vanni region. There is evidence to prove this. This story is based on the sufferings faced by the inhabitants of Vanni due to the tributes paid to the dutch by Vanni chieftains. The hierarchical relationship among Dutch, Vanni chieftains and the inhabitants of Vanni mostly affected the inhabitants. This story is about one of the victims of the inhabitants during the colonial period.Vellappanikan belongs to the Pannikar caste. They had the skill of taming the elephants, One of wife of Vellappanikan; Ariyaathai wsa appointed to catch a tusker by the chieftains. Then Ariyaathai went to the dark forest and used her psychic power and the tusker fell down. At the very end, Ariyaathai and the tusker died. It is an exceptional text that Vellappanikan – husband of Ariyaathailamented for his wife Ariyaathai. Earlier this story was composed in the elegiac form; written on the palm leaf. Then later lament was altered and edited in the various socioculture context and also it was composed in koothu aqnd other genreas of theater forms.This research analyses and compares the different versions of this story. The structural method will be used to understand the changes in detail. The historical background, the lament – voice of the weak, reflecting the histories, politics of the story of Ariyaathai will be analyzed.It is one of the rare portrayals of woman characters with psychological depth. In this lament the trauma of the inhabitants is recorded and also later this story was used for socio-cultural politics of the Vanni region.
Keywords: Structural method; Voice of the oppressed; Psych portrayal of woman